Determinants of Target Dividend Payout Ratio: A Panel ARDL Analysis - Demirgüneş, Kartal (International Journal of Economics and Financial Issues, 2015)
The aim of this study is to find out the determinants of target dividend payout ratio of BIST-listed firms operating in the non-metallic products (cement) manufacturing industry in the period of 2002-2012. Through this aim, the short and long-run effects of factors related to profitability, liquidity, growth, risk, market expectations and taxation on target dividend payout ratio is analyzed via panel ARDL methodology. Empirical findings indicate that in the long-run, factors related to profitability, growth and corporate taxation significantly affect target dividend payout ratio negatively; while factors related to risk and market expectations have statistically significant and positive effects on target dividend payout ratio. Additionally, in the short-run only profitability seems to have statistically significant and positive effect on the dependent variable. Keywords: Target Dividend Payout Ratio; Dividend Payout Policy; Panel ARDL Methodology. JEL Classifications: C33; G35; L61